Up in smoke: demarketing and consumer smoking cessation. (19th June 2015) - White, Christopher J.; Thomas, Harrison
Abstract: The concept of demarketing refers to the use of marketing techniques to reduce or eliminate demand for a product or service. A review of the demarketing literature relating to health and specifically antismoking initiatives indicated that, while research on this topic exists, much of it is not grounded in an acceptable attitudinal or behavioural theory. After determining the importance placed by a sample of 18–24‐year olds on nine demarketing initiatives, two dimensions were identified that best explained this construct. Items within these dimensions were summed and averaged to form single variables, which were then used to form the attitudinal component of the Model of Goal Directed Behaviour. The findings showed that two of these variables – one that captured product packaging aspects and another that consisted of place and price items – significantly influenced the desire to quit and indirectly influenced the intention to quit. Anticipated positive emotions, frequency of quitting attempts and perceived control over quitting also positively influenced the desire and/or intention to quit. The article concludes with a discussion that interprets these findings from a theoretical and practical perspective and suggests directions for future research.